2022
DOI: 10.1021/jacs.2c03196
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity in Dimension-Controlled Assemblies of Tetrahedral Gold Nanocrystals

Abstract: Polyhedron packings have fascinated humans for centuries and continue to inspire scientists of modern disciplines. Despite extensive computer simulations and a handful of experimental investigations, understanding of the phase behaviors of synthetic tetrahedra has remained fragmentary largely due to the lack of tetrahedral building blocks with tunable size and versatile surface chemistry. Here, we report the remarkable richness of and complexity in dimension-controlled assemblies of gold nanotetrahedra. By tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…The NC surface was well-passivated by the compact and densely packed saturated alkyl chains of MUA (Table S1 and Figure S3), which maximally preserves the tetrahedral shape of NCs. Deprotonated MUA ligands provide a balance between electrostatic repulsion and van der Waals attraction to impart hard particle-like interactions …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NC surface was well-passivated by the compact and densely packed saturated alkyl chains of MUA (Table S1 and Figure S3), which maximally preserves the tetrahedral shape of NCs. Deprotonated MUA ligands provide a balance between electrostatic repulsion and van der Waals attraction to impart hard particle-like interactions …”
Section: Resultsmentioning
confidence: 99%
“…■ RESULTS AND DISCUSSION Synthesis of Quasicrystalline Supracrystals. We synthesized single-crystalline gold nanotetrahedra bound by four {111} NC facets following previously reported seed-mediated growth methods with modifications 29,30 (Figures S1 and S2). The sharpness of nanotetrahedron vertices, which is quantified by the degree of truncation parameter t defined in Figure 1a, is evident from the representative HAADF-STEM image (Figure 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye's group reported that tetrahedral gold nanocrystals can be assembled into various ordered superstructures by controlling the surface chemistry of Au tetrahedra. 16 Besides 2D superlattices, 3D superlattices have long-range translational and orientational ordering. 17 3D superlattices comprising Au triangular nanoprisms and pentagonal Au bipyramids also exhibited orientation-dependent SERS activity.…”
Section: Introductionmentioning
confidence: 99%
“…Assembling colloidal nanoparticles into long-range ordered superlattices has been spotlighted as a promising pathway to creating structured materials with varying degrees of complexity and potentially programmable functionalities. , The properties of self-assembled materials rely heavily on the particle alignment and orientation, which profoundly influence their properties and applications in the field of optics, magnetics, and mechanics. Nonspherical, anisotropic nanoparticles are appealing building blocks for constructing superlattices with both positioning and orientational order, due to the directional energetic and entropic interactions induced by particle shape. Among various anisotropic building blocks, nanoparticles with concave features are of particular interest because of their rich phase behavior made possible by their distinct geometric curvature. Manna and co-workers synthesized colloidal CdSe-CdS octapods and obtained three-dimensional (3D) superlattices comprising interlocked particle chains under appropriate assembly conditions . Murray and co-workers realized linear liquid-crystalline superlattices based on the unidirectional assembly of Gd 2 O 3 tripodal nanoplates, and the structural diversity of the resulting superlattices could be further enriched upon coassembly of shape-complementary tripodal and rhombic nanoplates …”
mentioning
confidence: 99%